(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article presents the path and results of the research project Colonization and Design Education in Brazil – an analysis of the Fashion Design program curriculum at the Federal University of Ceará (UFC), developed within the NAÏF – Center for Studies in Art, Innovation, Fashion and Design. The qualitative, action research– based study used the methodology of life history and formative narratives as a critical-reflective tool for analyzing fashion education. It sought to understand how the coloniality of knowledge manifests itself in fashion design curricula and to propose decolonial pedagogical practices. Among the main outcomes are the publication of Decolonial Zine: Fashion and Decoloniality in Brazil, produced in partnership with the Research Collective for Decoloniality and Fashion (Netherlands), and the creation of the course Fashion and Activism, which expands the debate on diversity representation and epistemologies of the South in the field of fashion.